O narrador em O livro grande de Tebas, navio e Mariana, de Mário de Carvalho - Silveira, Pedro Rogério Tavares da (2024)
This dissertation aims at analyzing the narrator of the novel O livro grande de Tebas, navio e Mariana (1982), by Mário de Carvalho (1944-). After contextualizing the author’s fictional production, presenting its main characteristics and indicating some critical perspectives that are notable about it and suggest possible paths for its study, the work is divided into two chapters: the first focuses on a brief discussion of Tebas unstable relationship with the novel genre and offers some approximations between its fictional material and other literary works; and in the second, where it describes and examines the narrative, it dedicates itself to the analysis of the narrator, emphasizing his multiplicity, always based on concrete examples from the text. As a basis of analysis, in addition to comparisons with Carvalho’s criticism and with more specific or sparse theoretical-critical notions, are central the essays “Der Erzähler” by Walter Benjamin (1892-1940) and, above all, “Discours du récit” by Gérard Genette (1930-2018).